Penerapan Teknologi Pompa Irigasi Pertanian Bertenaga Surya di Desa Dukuhdempok Kecamatan Wuluhan Kabupaten Jember - Yuli Hananto; Zeni Ulma; Alex Taufiqurrohman Zain; Michael Joko Wibowo; Risse Entikaria Rachmanita (Indonesian Journal Publisher, 2023)
The conversion of agricultural land is an issue that needs attention because of the community's dependence on the agricultural sector and a serious threat to national food security with permanent impacts. Difficulty in irrigating agricultural land is one of the triggering factors for increasing land conversion, then a technology is needed to overcome this problem. The purpose of the implementation of this community service is to make irrigation system support equipment by utilizing renewable energy, namely solar panels. Solar panels are used as an energy source to drive the pump. To find out the effectiveness of the manufacture of solar-powered irrigation pumps, a performance test of the tool is carried out, namely testing of energy gain and water discharge. The solar-powered irrigation pump with a capacity of 800 Wp can operate properly which results in an average energy gain of 940.4 Wh with an average discharge gain of 1.84 liters/second.